Reforma estudiantil de córdoba (1918) y mayo de 1968. Evocación, celebración o nostalgia. A los cien y cincuenta años de dos eventos emancipatorios (2018)
ABSTRACT: This year commemorates events that are impossible to pass unnoticed for today’s citizens. Two hundred years ago Karl Marx was born, a critical and modern thinker who is still alive in many of his theses on the capitalist world. Similarly, the first proletarian revolutions took place 150 years ago in France and then throughout Europe. In 1898, the French writer Emile Zola, wrote a series of articles and the most representative of all of them, the written I Accuse, the truth is underway, with which a letter of citizenship was given to intellectuals in a modern sense. Nonconformity or antisystemic movements to say it with Imannuel Wallerstein, are part of a double sense of the modern capitalist world, as a revolution and as hope. This article seeks to reconstruct and make current two world events: the student reform of Córdoba in Latin America and May of 68 in France, events that marked our conscience, identities and political aspirations to this day. Evoke, celebrate or remember them with nostalgia, is the objective of this writing.